The effects of heterospecifics and climatic conditions on incubation behavior within a mixed‐species colony. (29th December 2015) - Coates, Peter S.; Brussee, Brianne E.; Hothem, Roger L.; Howe, Kristy H.; Casazza, Michael L.; Eadie, John M.
Abstract : Parental incubation behavior largely influences nest survival, a critical demographic process in avian population dynamics, and behaviors vary across species with different life history breeding strategies. Although research has identified nest survival advantages of mixing colonies, behavioral mechanisms that might explain these effects is largely lacking. We examined parental incubation behavior using video‐monitoring techniques on Alcatraz Island, California, of black‐crowned night‐heron Nycticorax nycticorax (hereinafter, night‐heron) in a mixed‐species colony with California gulls Larus californicus and western gulls L. occidentalis . We first quantified general nesting behaviors (i.e. incubation constancy, and nest attendance), and a suite of specific nesting behaviors (i.e. inactivity, vigilance, preening, and nest maintenance) with respect to six different daily time periods. We employed linear mixed effects models to investigate environmental and temporal factors as sources of variation in incubation constancy and nest attendance using 211 nest days across three nesting seasons (2010–2012). We found incubation constancy (percent of time on the eggs) and nest attendance (percent of time at the nest) were lower for nests that were located < 3 m from one or more gull nest, which indirectly supports the predator protection hypothesis, whereby heterospecifics provide protection allowing more time for foraging and other self‐maintenance activities. To our knowledge, this is the first empirical evidence of the influence of one nesting species on the incubation behavior of another. We also identified distinct differences between incubation constancy and nest attentiveness, indicating that these biparental incubating species do not share similar energetic constraints as those that are observed for uniparental species. Additionally, we found that variation in incubation behavior was a function of temperature and precipitation, where the strength of these effects was dependent on the time of day. Overall, these findings strengthen our understanding of incubation behavior and nest ecology of a colonial‐nesting species.